Preoperative Prevalence of Staphylococcus aureus in Cardiothoracic and Neurological Surgical Patients - Kapoor, Ritu; Barnett, Christopher J.; Gutmann, Rebecca M.; Yildiz, Vedat O.; Joseph, Nicholas C.; Stoicea, Nicoleta; Reyes, Stephan; Rogers, Barbara M. (Frontiers in Public Health, 2014)
Methicillin-resistant Staphylococcus aureus (MRSA) is a global cause of both hospital and community-acquired infection. This retrospective, observational study determined the prevalence of MRSA carriers in cardiothoracic and neurological surgical patients presenting to an outpatient preoperative assessment center in Columbus, OH. MRSA may cause aggressive skin and soft-tissue infection with potentially fatal complications, and cardiothoracic and neurological surgical patients are at high risk for surgical-site infection. Results indicated that 4.25% of the sample carried MRSA and 25.25% carried methicillin-sensitive Staphylococcus aureus.